Formation of the digital ecosystem of industrial cooperation based on advanced digital platforms in the context of reindustrialization - O. E. Pudovkina (Вестник университета)
An approach to the process of forming a digital ecosystem in industry in the context of digitalization has been presented. The aim of the study is to develop recommendations on the formation of a digital ecosystem of industrial cooperation based on the use of the technical capabilities of digital platforms in the context of the expansion of the digital industry. The result of the study is a digital ecosystem based on the theory of a new industrial society. The article emphasizes that advantage of reindustrialization for industry is to use a digital platform and to work with big data. The generated results will contribute to scientific research aimed at implementing digital transformation programs for industrial enterprises.